Evaluation of the in vivo genotoxicity of liposomal formulation for delivering anticancer estrogenic derivative (ESC8) in a mouse model - Ajaz Ahmad; Basit Latief Jan; Mohammad Raish; Hari Krishna Reddy Rachamalla; Rajkumar Banerjee; Debabrata Mukhopadhyay; Khalid M. Alkharfy (Elsevier, 2019)
The genotoxic potential of glucocorticoid receptor (GR)-targeted liposomal formulations of the anticancer drug molecule ESC8 was studied in vivo. A methodical literature review discovered no previous studies on the genotoxicity of ESC8. Genotoxicity was assessed in both male and female mice by various assay systems, such as comet assay, chromosomal aberrations and micronuclei assay, which detect different abnormalities. Eleven groups of male mice and eleven groups of female mice, containing six animals per group, were used in the present study: group I served as vehicle control; group II received the positive control (cyclophosphamide 40 mg/kg; CYP); and animals in group III to XI received free drug (ESC8), DX liposome and drug-associated DX liposomal formulation (DXE), respectively, dissolved in 5% solution of glucose at a drug-dose of 1.83, 3.67 and 7.34 mg/kg, respectively. Same drug treatments were followed for the female mice groups. The obtained data revealed the safety of DXE, which did not show substantial genotoxic effects at different dose levels. In contrast, the positive control, CYP, exhibited highly substantial irregular cytogenetic variations in comparison with the control group in different assays. Keywords: Liposomal formulation (DXE), Comet assay, Micronuclei, Chromosomal aberrations, Cyclophosphamide